Ileal FGF15 contributes to fibrosis‐associated hepatocellular carcinoma development. Issue 10 (6th November 2014) - Uriarte, Iker; Latasa, M. Ujue; Carotti, Simone; Fernandez‐Barrena, Maite G.; Garcia‐Irigoyen, Oihane; Elizalde, Maria; Urtasun, Raquel; Vespasiani‐Gentilucci, Umberto; Morini, Sergio; de Mingo, Alvaro; Mari, Montserrat; Corrales, Fernando J.; et al.
<x xml:space="preserve">Abstract</x> Fibroblast growth factor 15 (FGF15), FGF19 in humans, is a gut‐derived hormone and a key regulator of bile acids and carbohydrate metabolism. FGF15 also participates in liver regeneration after partial hepatectomy inducing hepatocellular proliferation. FGF19 is overexpressed in a significant proportion of human hepatocellular carcinomas (HCC), and activation of its receptor FGFR4 promotes HCC cell growth. Here we addressed for the first time the role of endogenous Fgf15 in hepatocarcinogenesis. Fgf15+/+ and Fgf15−/− mice were subjected to a clinically relevant model of liver inflammation and fibrosis‐associated carcinogenesis. Fgf15−/− mice showed less and smaller tumors, and histological neoplastic lesions were also smaller than in Fgf15+/+ animals. Importantly, ileal Fgf15 mRNA expression was enhanced in mice undergoing carcinogenesis, but at variance with human HCC it was not detected in liver or HCC tissues, while circulating FGF15 protein was clearly upregulated. Hepatocellular proliferation was also reduced in Fgf15−/− mice, which also expressed lower levels of the HCC marker alpha‐fetoprotein (AFP). Interestingly, lack of FGF15 resulted in attenuated fibrogenesis. However, in vitro experiments showed that liver fibrogenic stellate cells were not direct targets for FGF15/FGF19. Conversely we demonstrate that FGF15/FGF19 induces the expression of the pro‐fibrogenic and pro‐tumorigenic connective tissue growth factor (CTGF) in hepatocytes. These findings suggest the existence of an FGF15‐triggered CTGF‐mediated paracrine action on stellate cells, and an amplification mechanism for the hepatocarcinogenic effects of FGF15 via CTGF production. In summary, our observations indicate that ileal FGF15 may contribute to HCC development in a context of chronic liver injury and fibrosis.